Teaching Pronunciation: A Critical Assessment of the Role of Instructors - zanyar ghafar (MultiTech Publisher, 2023)
Teaching English Pronunciation poses challenges due to several factors. Educators encounter a lack of definitive norms and are confronted with inconsistent approaches when it comes to instructing pronunciation. This study critically examines many significant aspects pertaining to the education of English pronunciation. The objectives of this study are to provide a comprehensive definition of the term pronunciation, analyze the objectives of pronunciation instruction, elucidate the significance of pronunciation instruction, expound upon the responsibilities of teachers in facilitating pronunciation learning, and ultimately propose recommendations to assist teachers in enhancing learners' pronunciation skills. The literature evaluation indicates that in order to effectively teach pronunciation, it is essential for instructors to get proper training in pronunciation education.